2020
DOI: 10.1101/2020.04.26.20073569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regressing SARS-CoV-2 sewage measurements onto COVID-19 burden in the population: a proof-of-concept for quantitative environmental surveillance

Abstract: SARS-CoV-2 is an RNA virus, a member of the coronavirus family of respiratory viruses that includes SARS-CoV-1 and MERS. COVID-19, the clinical syndrome caused by SARS-CoV-2, has evolved into a global pandemic with more than 2,900,000 people infected. It has had an acute and dramatic impact on health care systems, economies, and societies of affected countries within these few months. Widespread testing and tracing efforts are employed in many countries in order to contain and mitigate this pandemic. Recent da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 21 publications
2
74
0
4
Order By: Relevance
“…Sewage monitoring had already been established as a tool to detect existing threats from pathogens, particularly for polio virus (Anis et al, 2013;Berchenko et al, 2017;Brouwer et al, 2018;WHO, 2003). And within a few short months after the emergence of Covid-19, the first pilot studies began to appear for WBE's possible use as a tool for tracking Covid-19 (e.g., Ahmed et al, 2020;Bar Or et al, 2020;La Rosa et al, 2020;Medema et al, 2020;Nemudryi et al, 2020;Randazzo et al, 2020aRandazzo et al, , 2020bWu et al, 2020b;Wurtzer et al, 2020). However, much more research will be required for its full development.…”
Section: What Randd Is Needed To Advance Wbe As a Valuable Public Healtmentioning
confidence: 99%
See 2 more Smart Citations
“…Sewage monitoring had already been established as a tool to detect existing threats from pathogens, particularly for polio virus (Anis et al, 2013;Berchenko et al, 2017;Brouwer et al, 2018;WHO, 2003). And within a few short months after the emergence of Covid-19, the first pilot studies began to appear for WBE's possible use as a tool for tracking Covid-19 (e.g., Ahmed et al, 2020;Bar Or et al, 2020;La Rosa et al, 2020;Medema et al, 2020;Nemudryi et al, 2020;Randazzo et al, 2020aRandazzo et al, , 2020bWu et al, 2020b;Wurtzer et al, 2020). However, much more research will be required for its full development.…”
Section: What Randd Is Needed To Advance Wbe As a Valuable Public Healtmentioning
confidence: 99%
“…Addressing each of these points would be required for calibrating any WBE monitoring method so that data could be related to actual per capita infection rates. A number of different means have been proposed, the inverse regression of qPCR cycle thresholds with known infection rates being one example (Bar Or et al, 2020). Only if calibration could be achieved, would WBE then be able to reliably estimate the total number of infected people at any given time.…”
Section: What Randd Is Needed To Advance Wbe As a Valuable Public Healtmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of SARS-CoV-2, considering that the virus was found both in stool samples and wastewater as previously described, several authors have proposed to use WBE as a tool to monitor the pandemic [ 41 , [76] , [77] , [78] , [79] , [80] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] ]. Thus, Medema et al [ 38 ] reported that sewage surveillance could be a sensitive tool to monitor SARS-CoV-2 circulation in the population since it could be detected prior to symptoms being reported in the local population.…”
Section: Wastewater Based Epidemiologymentioning
confidence: 99%
“…10.19.20215244 doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice. 8 School of Public Health, Sackler Faculty of Medicine, Tel-Aviv University, Tel-Aviv, Israel 9 KANDO, Environment Services Ltd, Tsor St 8, Kokhav Ya'ir Tzur Yigal, Israel. 10 Unit of Environmental Engineering, Ben-Gurion University of the Negev, Beer-Sheva,…”
mentioning
confidence: 99%